Forging subregional links in transportation and logistics in South Asia - Subramanian, Uma.; Arnold, John, 1946- (Washington, D.C. : World Bank, 2001)
"In the wake of recent liberalization, South Asian countries are seeking to expand trade and investment links with regional and global partners. However, inadequate infrastructure combined with policy and regulatory constraints imposes significant limitations in opening up one of the poorest regions in the world.".
"Forging Subregional Links in Transportation and Logistics in South Asia examines transportation and logistics issues in Bangladesh, Bhutan, eastern India, and Nepal and provides well-researched commentary on non-tariff barriers that impede the seamless flow of goods and services to regional and global markets. Besides offering a wealth of information on regional transportation issues, the book offers an innovative analytic framework and a comprehensive analysis of the hidden costs associated with logistics barriers in South Asia. Detailed commodity case studies provide a strong quantitative argument that the flows and cost of goods traded within and outside the region are adversely affected by physical infrastructure bottlenecks as well as by policy anomalies.".
"Written for public and private sector professionals in South Asia, the book presents policy options that would enable the subregion to compete in a rapidly changing global environment. While the book is designed to stimulate informed dialogue among key stakeholders, the unique approach and lessons learned have broad applications of interest to a wider audience."--BOOK JACKET.
Includes bibliographical references (p. 117-120).
Keywords: Transportation -- South Asia; Regionalism -- South Asia; South Asia -- Economic conditions